2019
DOI: 10.2106/jbjs.19.00130
|View full text |Cite
|
Sign up to set email alerts
|

Use of Standardized Letters of Recommendation for Orthopaedic Surgery Residency Applications

Abstract: Introduction ii Copyright ©2018 NRMP. Reproduction prohibited without the written permission of the NRMP. Background The first edition of Charting Outcomes in the Match was published in August 2006 to document how applicant qualifications affect success in the Main Residency Match®. The report was published biennially between and 2011 and was a collaboration of the National Resident Matching Program® (NRMP®) and the Association of American Medical Colleges® (AAMC®). Match outcome data from the NRMP were combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Although studies on gender differences in LOR to orthopaedic surgery have been performed previously 20 , 21 , there are no previous studies evaluating racial differences in LOR in orthopaedic surgery. Day et al 22 found that Asian American, African American, Hispanic, and Latino residents constituted only 19.8% of orthopaedic surgery residents in 2006, which was significantly lower than that found in general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on gender differences in LOR to orthopaedic surgery have been performed previously 20 , 21 , there are no previous studies evaluating racial differences in LOR in orthopaedic surgery. Day et al 22 found that Asian American, African American, Hispanic, and Latino residents constituted only 19.8% of orthopaedic surgery residents in 2006, which was significantly lower than that found in general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some opportunities for improvement include the implementation of implicit bias training for both members of residency selection committees as well as faculty who are asked to write LORs. Standardized LORs which have been adopted by emergency medicine [11], orthopedic surgery [31], and otolaryngology [32] are other means to increase objectivity in the application but do have the caveats of a limited narrative and fewer opportunities to disclose specific skills or anecdotes. Others in RO have been outspoken about deemphasizing "away" rotations and faculty LORs to create a more even playing field across students of varying socioeconomic backgrounds [33].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the coronavirus 2019 (COVID-19) pandemic added an unforeseen complication to the orthopaedic residency match [1,7]. Although much of the application process remained unchanged, including the importance of board examination scores (this is scheduled to change in January 2022, when the United States Medical Licensing Examination [USMLE] Step 1 will convert to pass-fail scoring), clinical grades, and letters of recommendation, away rotation and in-person interview performance were not available during 2021 [5,8,18,21,25,31,33,34,37]. During the pandemic, the Association of American Medical Colleges [2] and Council of Orthopaedic Residency Directors [6] recommended that orthopaedic surgery residency programs cancel away rotations and in-person interviews for the 2021 residency application cycle.…”
Section: Introductionmentioning
confidence: 99%